New characteristics and applications of the EP, normal and Hermitian matrices - Liu, Xiaoji; Hao, Huijia (Italian Journal of Pure and Applied Mathematics, 2025)
In this paper, we present the EP-matrices, normal, and new features of the Hermitian matrix. We are going to push it to a higher order form. This paper describes EP-matrices, normal matrices and Hermitian matrix equivalent forms by using Core inverse. We also give several special equivalent facts by use decompositions. We also give other special equivalent facts. A new equivalent condition for the reverse order law is also obtained.